2022
DOI: 10.21037/sci-2022-026
|View full text |Cite
|
Sign up to set email alerts
|

Creation of human hematopoietic chimeric cell (HHCC) line as a novel strategy for tolerance induction in transplantation

Abstract: Background: Cell-based and chimerism-based therapies represent a promising approach for tolerance induction in transplantation. We propose a new cell therapy of the ex vivo created human hematopoietic chimeric cells (HHCC) as an alternative approach to bone marrow (BM)-based therapies in support of solid organ and vascularized composite allotransplantation (VCA). This study aimed to characterize in vitro the phenotype, genotype, clonogenic, and tolerogenic properties of HHCC.Methods: Thirty ex vivo fusions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…Inspired by the potential of the encouraging outcomes of the rat DRCCs, our Microsurgery Laboratory successfully created HHCC from the BM-derived CD34 + cells originating from two unrelated human donors, according to the previously described protocol ( 36 ). The properties of the HHCC originating from human CD34 + cells were characterized in vitro , confirming the tolerogenic properties of HHCC and the potential application of HHCC therapy for tolerance induction in BM, solid organs, and VCA transplantation ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inspired by the potential of the encouraging outcomes of the rat DRCCs, our Microsurgery Laboratory successfully created HHCC from the BM-derived CD34 + cells originating from two unrelated human donors, according to the previously described protocol ( 36 ). The properties of the HHCC originating from human CD34 + cells were characterized in vitro , confirming the tolerogenic properties of HHCC and the potential application of HHCC therapy for tolerance induction in BM, solid organs, and VCA transplantation ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are several similarities between our two hematopoietic lines—the HHCC and HUDC cell line of created human chimeric cells. Both lines represent cells of the human hematopoietic lineage origin and both contain rich sources of the HSCs applicable for transplantation ( 36 ). When comparing the hematopoietic markers, the UCB cells have been shown to contain a high percentage of primitive stem cells, including very small embryonic-like stem cells, and a lower immunogenicity compared to other sources of stem cells, such as BM and PB ( 60 , 61 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a rat face transplant model, they found that DRCC up-regulated the gene expression of Il-10 which correlated with FoxP3 expression and an increased number of Treg. They compared different cell-based therapies and the longest allograft survival without continuous immunosuppression was observed in group supported by DRCC therapy [14,37,74] Siemionow et al also developed a human hematopoietic chimeric cell (HHCC) line from two unrelated bone marrow donors, demonstrating the feasibility and reproducibility of the technique [75 ▪▪ ]. They characterized the HHCC, confirming high viability and immunomodulatory effects highlighting HHCC application as a novel and effective cell-based therapeutic strategy for chimerism and tolerance induction in VCA and solid organs transplantation.…”
Section: Cell- Based Strategies For Immunomodulation In Vascularized ...mentioning
confidence: 99%